Lead-mediated highly diastereoselective allylation of aldehydes with cyclic allylic halides - Cheng, Bu-Qing (2021)
Lead was found to efficiently mediate the allylation reactions of carbonyl compounds with cyclic allylic halides in the presence of stoichiometric amounts of lithium chloride and a catalytic amount of GaCl3 (20 mol %), leading to the desired homoallylic alcohols in modest to high yields with excellent diastereocontrol (>99:1 syn/anti) and good functional group tolerance. In contrast, the use of either 2-pyridinecarboxaldehyde as the carbonyl substrate or ( E)-cinnamyl bromide as the allylating agent produced the corresponding product with reversed diastereoselectivity (>99:1 anti/syn).